INNOVATIVE APPROACH TO THE LESSON PROCESS IN THE TRAINING SYSTEM - P. Davronov; M. Rahimkulova (International Journal of Innovations in Engineering Research and Technology, 2021)
This article provides information on innovative approaches to the organization of training in the training system.